2016
DOI: 10.3389/fpls.2016.01280
|View full text |Cite
|
Sign up to set email alerts
|

Over-expression of Topoisomerase II Enhances Salt Stress Tolerance in Tobacco

Abstract: Topoisomerases are unique enzymes having an ability to remove or add DNA supercoils and untangle the snarled DNA. They can cut, shuffle, and religate DNA strands and remove the torsional stress during DNA replication, transcription or recombination events. In the present study, we over-expressed topoisomerase II (TopoII) in tobacco (Nicotiana tabaccum) and examined its role in growth and development as well as salt (NaCl) stress tolerance. Several putative transgenic plants were generated and the transgene int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Immunostaining data revealed a lower DNA methylation pattern in response to abiotic stress. Furthermore, the expression level of DNA topoisomerases was upregulated in response to both salinity and drought stress, which is corroborated by other studies (Hettiarachchi et al, 2005; John et al, 2016). High level of the DNA topoisomerase in maize seedlings exposed to abiotic stresses reflects that abiotic stress induces DNA damage (Huang et al, 2003; Morotomi‐Yano et al, 2018), cell cycle arrest, and apoptosis (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Immunostaining data revealed a lower DNA methylation pattern in response to abiotic stress. Furthermore, the expression level of DNA topoisomerases was upregulated in response to both salinity and drought stress, which is corroborated by other studies (Hettiarachchi et al, 2005; John et al, 2016). High level of the DNA topoisomerase in maize seedlings exposed to abiotic stresses reflects that abiotic stress induces DNA damage (Huang et al, 2003; Morotomi‐Yano et al, 2018), cell cycle arrest, and apoptosis (Wang et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…CDK/CYC complex activation is also altered by the upregulation of WEE1 kinase, which is associated with the stress response. Red background color refers to strongly upregulated genes and green background color refers to strongly downregulated genes, whereas black backgrounds indicate no transcription changes drought stress, which is corroborated by other studies (Hettiarachchi et al, 2005;John et al, 2016). High level of the DNA topoisomerase in maize seedlings exposed to abiotic stresses reflects that abiotic stress induces DNA damage (Huang et al, 2003;Morotomi-Yano et al, 2018), cell cycle arrest, and apoptosis (Wang et al, 2016).…”
Section: Salinity and Drought Stress Upregulate The Expression Of Dna Topoisomerasessupporting
confidence: 70%
“…DNA replication is the biological process by which can exact copy of a DNA molecule is created and genetic information is faithfully transmitted in all living organisms. It is evident that salinity stress affects the cellular molecules involved in DNA replication including helicases, DNA polymerase and DNA replication licensing factor (Sanan-Mishra et al, 2005;John et al, 2016). In our study, transcriptomic analysis also showed that several DEG S required for DNA replication process were only up-regulated in the leaves of sugar beet treated with high neutral salt.…”
Section: Deg S Involved In the Sugar Beet Specific Response To High Lsupporting
confidence: 59%
“…To date, ve DDR pathways (base combination repair (BER), nucleotide recombination repair (NER), mismatch repair (MMR), homologous recombination repair (HR), and nonhomologous end-joining (NHEJ) have been reported (Chatterjee and Walker 2017;Nisa et al 2019). It has been demonstrated that salinity stress affects the cellular processes involved in DNA replication (Geng et al 2020;John et al 2016;Sanan-Mishra et al 2005). Our study observed that the CAR gene (MS.gene031323.t1) required for DNA replication, mismatch repair, nucleotide excision repair and homologous recombination was down-regulated in GN but signi cantly up-regulated in AG (Table 1).…”
Section: Physiological Regulation In Response To Alkaline Stressmentioning
confidence: 99%